Purslane—Portulaca oleracea L. - James M. Stephens (EDIS)
This document provides an overview of purslane (Portulaca oleracea L.), a succulent summer annual plant often considered a weed but occasionally consumed as a vegetable. Native to Persia and introduced to the U.S. from Europe, purslane is now common in Florida. It features fleshy stems and leaves, and can be eaten raw or cooked. The plant reproduces via seeds and stem fragments, and while wild forms are widespread, cultivated varieties are rare in seed catalogs. Original publication date May 1994.